Gain‐of‐function experiments with bacteriophage lambda uncover residues under diversifying selection in nature. (11th September 2018) - Maddamsetti, Rohan; Johnson, Daniel T.; Spielman, Stephanie J.; Petrie, Katherine L.; Marks, Debora S.; Meyer, Justin R.
Abstract: Viral gain‐of‐function mutations frequently evolve during laboratory experiments. Whether the specific mutations that evolve in the lab also evolve in nature and whether they have the same impact on evolution in the real world is unknown. We studied a model virus, bacteriophage λ, that repeatedly evolves to exploit a new host receptor under typical laboratory conditions. Here, we demonstrate that two residues of λ's J protein are required for the new function. In natural λ variants, these amino acid sites are highly diverse and evolve at high rates. Insertions and deletions at these locations are associated with phylogenetic patterns indicative of ecological diversification. Our results show that viral evolution in the laboratory mirrors that in nature and that laboratory experiments can be coupled with protein sequence analyses to identify the causes of viral evolution in the real world. Furthermore, our results provide evidence for widespread host‐shift evolution in lambdoid viruses.